Latex allergy in clinical practice - R Pradeep Kumar (Wolters Kluwer Medknow Publications, 2012)
A continuous exposure or contact to latex products may sensitize the human body by causing mild to fatal reactions. Despite the availability of the literature, medical personnel are still unaware of the implications of the use of latex materials. The increased awareness to prevent the transmission of infectious blood borne pathogens has lead to increased usage of medical gloves among health care workers. This increased usage of medical gloves, along with improved methods in diagnosing latex allergy, has been the reason for the rise in the number of reported cases. This has lead to recognition of latex allergy as a serious medical concern. Patients in high-risk groups must be assessed carefully, so that appropriate protocols can be used to protect them from contact with latex.